The Impact of Consumer Empowerment on Customer Satisfaction in Banking - Abubakar Ally, Ahmed Baalwy (2014)
It is evident from the literature that linking customer empowerment to consumer satisfaction has become important. Customer involvement, firm’s responsiveness and face-to-face contact are the contexts measured for the above relationship. Consumer tastes, preferences, and behavior continuously change with time. There is wide recognition of the importance of customer empowerment and satisfaction. However, there is very limited literature that discusses impact of such relationship in the banking industry. The literature disregards the factors of customer involvement, firm’s responsiveness, and face to face contact, while it is considered that customer empowerment is major driver for consumer satisfaction. The objective of this research is to investigate the relationship between customer empowerment and customer satisfaction, and to study how this relationship is influenced by customer involvement, responsiveness to consumers, and face to face contact between the customer and employee. To achieve this objective, a quantitative approach will be used with questionnaire as tool. SPSS software is used for descriptive analysis and PLS estimation software was used to test the relationships among the constructs. The findings of the study indicate that customer empowerment has a positive impact on customer satisfaction and customer involvement. On the other hand, customer involvement has a negative insignificance on customer satisfaction. Whereas, firm’s responsiveness and face-to-face contact have an indirect moderating effect on customer satisfaction. The results contribute to the body of knowledge on the role of customer empowerment in banking.